Characteristics of pre-school children’s creative activity - Kotelianets, Natalka; Yuliia Kotelianets (Technium Social Sciences Journal, 2020)
The article deals with the problem of preschool children’ formation of the creative activity. The author understands creative activity as integrative, qualitative characteristic of personality, which includes a complex of motivational, creative, volitional components. According to the selected indicators, a diagnostic methodology for the three main blocks was constructed. All indicators were evaluated by a 3-point system, in which each score expressed the content of the existing level of formation of diagnosed indicators. Four levels of creative activity of older preschool children are distinguished: high (creative), middle (research), below average (imitative), low (performing). It is established that the most unformed components of creative activity in preschool age are creative and volitional. It is substantiated that development of speed, flexibility and originality of thinking, as well as stimulation of children’s initiative and independence will allow to increase the level of creative activity.